Wolność w wyborze dobra i zła - cnoty i grzechu - Paweł Góralczyk (Jesuit University Ignatianum in Krakow, 2017)
Evil, sin constitute reality still present in our lives. But contemporary man ﬁ nds it difﬁ cult to identify and localize evil. In order to recognize evil-sin, one has to see them in terms of a choice with reference to speciﬁ c order and ideal. Meanwhile, it appears from postmodernist assumptions that there is no objective truth and good, but only various opinions and options. Furthermore, the spiritual image of man living at the beginning of the 21st century is frequently characterized by confusion, uncertainty and lack of hope, which is connected with the loss of remembrance of Christian heritage, attitude of practical agnosticism and religious indifference. Many people appear to be deprived of spiritual base, like heirs who have squandered heritage left to them by history. Despite numerous enslavements, humankind has not lost the sense of evil and knows where this evil is situated. And this evil-sin is subject to incessant confrontation with good and virtue. But is there today a model of good and virtue? Yes - ﬁ rst of all, the model is Merciful God, who revealed Himself in Jesus Christ. Nowadays, in days of moral crisis, this state of tension and struggle for what has an authentic and objective moral value, it is what a Christian particularly needs. Since in many societies a false hierarchy of values is being established, where the chief place is occupied by such goods as success, usefulness, power and pleasure.